Differential responses to academic stress during the COVID-19 pandemic, transition, and the new normal period - Kurniawan, Luky; Sutanti, Natri; Aryani, Eka; Laras, Palasara Brahmani; Nuryana, Zalik; Nastain, Muhamad (Intelektual Pustaka Media Utama, 2024)
This study aimed to investigate decreasing student academic stress in distance learning during the COVID-19 pandemic, transition period, and new normal era by giving a self-help module to students. This research employed an experimental approach with a group pre-test post-test design with quantitative analytics. The perceived academic stress scale (PASS) and module evaluation scale were utilized to assess students' academic stress levels and their understanding of the module. The subjects consisted of one male student and thirty-seven female students, as the school was dominated by female students. This study indicated that students' academic stress levels during the pandemic and the new normal were in the medium range (18.82 - 19.97). The results showed that there was no significant difference in academic stress between the pandemic and the transition period (t = 1.322, p 0.05) and the data between the pandemic and the new normal (t = -1.426, p 0.05), while between the transition period and the new normal, it showed a significant difference (t = -4.189, p 0.05). The study recommends that schools develop future guidance and counseling programs to help students cope with stress and build resilience. This study's findings can inform policy decisions and academic interventions to support students' mental health and academic success during challenging times.